2002
DOI: 10.1159/000047187
|View full text |Cite
|
Sign up to set email alerts
|

In utero Exposure to Immunosuppressive Drugs

Abstract: The number of pregnant women receiving immunosuppressants for anti-rejection therapy or autoimmune diseases is increasing. All immunosuppressive drugs cross the placenta, raising questions about the long-term outcome of the children exposed in utero. There is no higher risk of congenital anomalies. However, an increased incidence of prematurity, intrauterine growth retardation (IUGR) and generally low birth weight has been reported, as well as maternal hypertension and preeclampsia. The most frequent neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 39 publications
(103 reference statements)
1
26
1
1
Order By: Relevance
“…It was first used in clinical trials 13 years ago at our center, and many other centers have confirmed our initial findings of safety and efficacy of the drug in clinical LTx (12). Its safety in pregnancy has been similarly described by us (5) and others (13)(14)(15)(16). It is important to note that this is a case series with only 39 mothers and 49 babies, and that it is premature to draw a firm conclusion.…”
Section: Fludrocortisonesupporting
confidence: 67%
“…It was first used in clinical trials 13 years ago at our center, and many other centers have confirmed our initial findings of safety and efficacy of the drug in clinical LTx (12). Its safety in pregnancy has been similarly described by us (5) and others (13)(14)(15)(16). It is important to note that this is a case series with only 39 mothers and 49 babies, and that it is premature to draw a firm conclusion.…”
Section: Fludrocortisonesupporting
confidence: 67%
“…Additionally, fetal and neonatal adverse effects in brain, kidney, lung skeleton, gastrointestinal tract and cardiovascular system have also been reported after the use of NSAIDs during prenatal (Antonucci et al, 2012;Boubred et al, 2006). Other drugs used by pregnant women during prenatal, like immunosuppressive drugs, are not associated with higher risk of congenital anomalies but can be associated with an increased incidence of prematurity, intrauterine growth retardation and low birth weight (Prévot et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Azathioprine concentration in the placenta is relatively high, reaching 64-93% of the concentration in the maternal serum. However, the concentration in fetal blood is much lower, and is 1-5% of that in the maternal serum [14][15][16]. Cyclosporine A cross the placenta, reaching about 5% fetal blood concentration compared to the concentration in the maternal serum [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentration in fetal blood is much lower, and is 1-5% of that in the maternal serum [14][15][16]. Cyclosporine A cross the placenta, reaching about 5% fetal blood concentration compared to the concentration in the maternal serum [14][15][16][17][18]. Systematic literature review published in 2016 by the European League Against Rheumatism shows compatibility with pregnancy and lactation for azathioprine, cyclosporine, tacrolimus and glucocorticosteroids [19].…”
Section: Discussionmentioning
confidence: 99%